1984
DOI: 10.1530/jrf.0.0720039
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of thecal and granulosa cell function during follicular development in the bovine ovary

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1
4

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 28 publications
(30 reference statements)
10
92
1
4
Order By: Relevance
“…magnification (McNatty et al 1984). These studies also found either a lower level of E 2 (Irving- Rodgers et al 2003b) or no significant reduction (McNatty et al 1984) respectively at these sizes of follicles.…”
Section: Atresia Of Antral Follicles !5 MM In Diametermentioning
confidence: 56%
See 1 more Smart Citation
“…magnification (McNatty et al 1984). These studies also found either a lower level of E 2 (Irving- Rodgers et al 2003b) or no significant reduction (McNatty et al 1984) respectively at these sizes of follicles.…”
Section: Atresia Of Antral Follicles !5 MM In Diametermentioning
confidence: 56%
“…Evidence of differential regulation also comes from theoretical considerations. It has been argued ) that during follicular development there is on average a net 19 doublings in the surface area of the follicle (from a primordial to an 18 mm bovine follicle, calculated from van Wezel & Rodgers (1996)), and a net 21 doublings of granulosa cell numbers (if 40 million granulosa cells were present as reported by McNatty et al (1984) -see van Wezel & Rodgers (1996). Thus, it is predicted in bovine that cell layers in the membrana granulosa would increase from one layer, as in primordial follicles, to four (calculated as (21-19) 2 Z4) layers , and this is close to the number of layers observed in bovine preovulatory follicles .…”
Section: Healthy Antral Folliclesmentioning
confidence: 99%
“…As atresia progresses, peribasal cells differentiate into luteal-like cells that express StAR and P450 side-chain cleavage and most likely are able to secrete progesterone. Supporting this concept, it has been shown that as bovine follicles undergo atresia, the progesterone content of the follicular fluid increases significantly (McNatty et al 1984b, Jolly et al 1994. However, the lack of apoptosis in peribasal granulosa cells is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In the cow, peripheral blood concentrations of androstenedione and oestradiol were reported to be similar during the follicular phase (McNatty et al, 1984). Since bovine follicles >2 mm in diameter secrete androstenedione in the follicular fluid (McNatty et al, 1984) it is likely that the androstenedione concentration is the result of the accumulated secretion by several follicles. Androstenedione is the main substrate for the aromatase and thus the primary precursor for oestradiol synthesis by bovine granulosa cells (Dieleman & Blankenstein, 1984).…”
Section: Discussionmentioning
confidence: 99%